Potential of non-skin oil palm particleboard as an alternative bench component for Kuala Lumpur International Airport - Rusli, Asa Naim (2006)
The design of airport benches plays a significant role in ensuring the comfort of passengers and visitors. In addition, it can portray the local image of the place. Furthermore, based on preliminary research, the current standard airport benches in the Kuala Lumpur International Airport (KLIA) do not give any special local identity that could impress ‘first time’ visitors to the country. In addition, the easily damaged cushion part of the existing benches has become a problem to KLIA’s maintenance as it is costly and could not be easily replaced. This research proposed the non-skin particleboard made from oil palm biomass as an alternative material to replace the cushion component of the existing benches. During the period of this research, the use of nonskin particleboard is still in the preliminary stages. The research methods adopted for the study are mixed method; quantitative and qualitative. The method for qualitative research includes interview,direct and participant observation, videotaping of subjects, case studies and document analysis. In this study, qualitative research deems more appropriate since many of the areas to be studied are subjective in nature (comfort, aesthetic and perception). The study found that the new material could solve the current problem faced by KLIA. The study also reveals that although there are different levels of acceptance among respondents from different background and profession, there is a good potential for non-skin particleboard to replace the easily damaged bench components based on its advantage in terms of aesthetic appearance. In addition, it is widely accepted that the new material could portray the Malaysian image. The potential of this material in other type of furniture is also proposed.